Pelaksanaan Perjanjian Bagi Hasil Tanah PertanianAntara Pemilik Tanah dengan Penggarap Tanah(Studi Kasus di Desa Kebonagung, Kecamatan Sidoharjo, Kabupaten Wonogiri) - Widyaningsih, Tyas; , Drs.Hj. Sri Arifah, SH, M.Pd (2016)
This study was intended to examine the implementation of revenue-sharing agreements between landowners of gricultural land with serf in Kebonagung Village, District Sidoharjo, Wonogiri. This study is a qualitative research that is descriptive. Sources of data obtained from several informants, places and events, as well as documents. Informants were selected in this study include: Head of Village, Farmers and agricultural laborers in the village Kebonagung, District Sidoharjo, Wonogiri. It is the background for the agreement for the produce of which is an agreement between landowners and tenants. The division of the produce using the term mertelu with a ratio of 1: 3, namely 25% for owners and 75% of land to the tiller. Because seeds, fertilizer, labor and so on from the tiller while the owner only provides field only to be managed by the tenants. The system is closer agreement with the customs prevailing in Kebonagung Village, District Sidoharjo, Wonogiri, because they are more flexible and simpler. Data collection techniques by using the method of observation, interviews, and documentation. By using this system are expected mertelu public welfare Kebonagung Village, District Sidoharjo, Wonogiri district, is getting better and prosperous.